Methodology for quantifying the volatile mixing state of an aerosol. Issue 8 (2nd August 2016) - Dickau, Matthew; Olfert, Jason; Stettler, Marc; Boies, Adam; Momenimovahed, Ali; Thomson, Kevin; Smallwood, Greg; Johnson, Mark
ABSTRACT: Mixing state refers to the relative proportions of chemical species in an aerosol, and the way these species are combined; either as a population where each particle consists of a single species ('externally mixed') or where all particles individually consist of two or more species ('internally mixed') or the case where some particles are pure and some particles consist of multiple species. The mixing state affects optical and hygroscopic properties, and quantifying it is therefore important for studying an aerosol's climate impact. In this article, we describe a method to quantify the volatile mixing state of an aerosol using a differential mobility analyzer, centrifugal particle mass analyzer, catalytic denuder, and condensation particle counter by measuring the mass distributions of the volatile and non-volatile components of an aerosol and determining how the material is mixed within and between particles as a function of mobility diameter. The method is demonstrated using two aerosol samples from a miniCAST soot generator, one with a high elemental carbon (EC) content, and one with a high organic carbon (OC) content. The measurements are presented in terms of the mass distribution of the volatile and non-volatile material, as well as measures of diversity and mixing state parameter. It was found that the high-EC soot nearly consisted of only pure particles where 86% of the total mass was non-volatile. The high-OC soot consisted of either pure volatile particles or particles that contained a mixture of volatile and non-volatile material where 8% of the total mass was pure volatile particles and 70% was non-volatile material (with the remaining 22% being volatile material condensed on non-volatile particles). © 2016 American Association for Aerosol Research